Mesenchymal stem cells ameliorate β cell dysfunction of human type 2 diabetic islets by reversing β cell dedifferentiation - Wang, Le (EBioMedicine, 2020)
BACKGROUND: A physiological hallmark of patients with type 2 diabetes mellitus (T2DM) is β cell dysfunction. Despite adequate treatment, it is an irreversible process that follows disease progression. Therefore, the development of novel therapies that restore β cell function is of utmost importance. METHODS: This study aims to unveil the mechanistic action of mesenchymal stem cells (MSCs) by investigating its impact on isolated human T2DM islets ex vivo and in vivo. FINDINGS: We propose that MSCs can attenuate β cell dysfunction by reversing β cell dedifferentiation in an IL-1Ra-mediated manner. In response to the elevated expression of proinflammatory cytokines in human T2DM islet cells, we observed that MSCs was activated to secret IL-1R antagonist (IL-1Ra) which acted on the inflammed islets and reversed β cell dedifferentiation, suggesting a crosstalk between MSCs and human T2DM islets. The co-transplantation of MSCs with human T2DM islets in diabetic SCID mice and intravenous infusion of MSCs in db/db mice revealed the reversal of β cell dedifferentiation and improved glycaemic control in the latter. INTERPRETATION: This evidence highlights the potential of MSCs in future cell-based therapies regarding the amelioration of β cell dysfunction.